Analysis of Even-Rodeh Code For Text Compression - Rian Syahputra (STMIK Budi Darma, 2020)
Text compression is used to reduce the repetition of letters so that the storage space used becomes smaller and transmission becomes faster. Techniques in text compression that can be used are using lossless compression. Lossless compression is a type of compression where when the decompression process occurs no data is lost. The Even-Rodeh Code algorithm is a lossless type of compression algorithm that replaces the initial bit code of the data with a code from the Even-Rodeh Code algorithm so that it can produce smaller data sizes